2015
DOI: 10.3791/53402
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Phagosome pH by Ratiometric Fluorescence Microscopy

Abstract: Phagocytosis is a fundamental process through which innate immune cells engulf bacteria, apoptotic cells or other foreign particles in order to kill or neutralize the ingested material, or to present it as antigens and initiate adaptive immune responses. The pH of phagosomes is a critical parameter regulating fission or fusion with endomembranes and activation of proteolytic enzymes, events that allow the phagocytic vacuole to mature into a degradative organelle. In addition, translocation of H + is required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…In conclusion, there are other methods available to measure phagosomal pH using different fluorescent dyes as Nunes et al . have demonstrated 13 as well as other groups 27 28 . Other researchers have also used S-1 to measure cytosolic pH 29 or phagosomal pH 14 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In conclusion, there are other methods available to measure phagosomal pH using different fluorescent dyes as Nunes et al . have demonstrated 13 as well as other groups 27 28 . Other researchers have also used S-1 to measure cytosolic pH 29 or phagosomal pH 14 .…”
Section: Discussionmentioning
confidence: 83%
“…A further significant problem with FITC in the context of neutrophils is that it is thought to be photobleached by MPO 12 . The MPO inhibitor, sodium azide, can be used to limit photobleaching 13 , but it has been shown that sodium azide directly lowers the phagosomal pH in an MPO-independent manner and is thus inappropriate for use in such assays 5 .…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether the decrease in OVA degradation in 3d/3d phagosomes reflected a change in endosomal/phagosomal acidification, we measured endosomal pH at 60 min after DCs incubation with 40 kDa dextrans coupled to pH-sensitive (FITC) or to pH-insensitive dyes (Alexa-647) 16 . Phagosomal pH was quantified via ratiometric imaging by exposing cells to FITC-coupled OVA-coated zymosan, as previously described 28 , 29 . Both endosomes and phagosomes from 3d/3d BM-DCs had increased pH compared to WT cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, if the universe is locked in the negative potential energy phase, it will keep on inflating. However, as shown in [2], depending upon the nature of the potential, one can exit primordial inflation through a classical transition from negative to positive potential regions, see also [3][4][5][6] for the study and implementation of similar mechanisms. To our knowledge, CI model was the first to realize a phenomenologically successful cosmology with negative potential energy 1 , and may have interesting implications * Electronic address: tbiswas@loyno.edu † Electronic address: tomik@astro.uio.no ‡ Electronic address: a.mazumdar@lancaster.ac.uk 1 For more recent efforts in this direction see [7], though ghost and tachyonic instabilities may develop in this proposal [8].…”
Section: Introductionmentioning
confidence: 99%
“…3 In general the infrared divergence of quantum fluctuations that could otherwise dominate over the thermal fluctuations may also be resolved in nonsingular cosmologies [26]. 4 For some of the other attempts to resolve the Big Bang/Big Crunch singularity through bounces when a high energy scale is reached, see [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%